VD_FINDINFO Jug / 2019 / 48 vom 20. September 2018 - VD Tribunal cantonal (2018)
LÉSION CORPORELLE SIMPLE, VOIES DE FAIT, MISE EN DANGER DE LA VIE D'AUTRUIART. 129 CP, DIRECTIVEINJONCTION | 123 ch. 1 CP, 123 ch. 2 al. 5 CP, 126 al. 1 CP, 126 al. 2 CP, 129 CP, 94 CP